The Effectiveness of Pilates in Improving Autonomic Regulation in Female Athletes of Complex Coordination Sports - Valentyna Todorova; Iryna Ruda; Oksana Kosianchuk; Olena Pogorelova; Svitlana Atamanyuk (Kharkiv State Academy of Physical Culture, 2024)
Purpose: To assess the impact of the developed Pilates program on the improvement of physical qualities and the functional state of the autonomic nervous system in female athletes of complex coordination sports in the preparatory period. Material and methods. The analysis of heart rate variability was utilized for female athletes of complex coordination sports at baseline and after 3 months of training in preparatory period. 36 female athletes of complex coordination sports (sports aerobics, n=26 and sports acrobatics) participated in the pedagogical experiment during the specialized basic training phase. The average age of the studied female athletes was 15.7 ± 0.5 years. The primary group comprised 18 athletes of complex coordination sports engaged in a regimen aimed at enhancing the functional condition of the autonomic nervous system (Pilates group). In contrast, the control group comprised 18 female athletes following the training program of yoga. The number of Pilates classes in the main group and yoga in the control group was the same and amounted to 36 classes. Results: at the end of the pedagogical experiment comparison of heart rate variability parameters revealed to significant differences between the main and control groups of female athletes of complex coordination sports for nearly all parameters. In the examined main group athletes of complex coordination sports the standard deviation of mean values (SDNN) was superior by 8.10 ms (p<0.001, t=6,15) compared to the control group. Additionally, the square root of the sum of the squares of differences in consecutive pairs of N-N intervals (RMSSD) showed improvement by 8.96 ms (p<0.001, t=5,94), the total power of regulatory systems (TP) was better by 298.40 ms² (p<0.001, t=8,97), the very low-frequency component of the spectrum (VLF) was superior by 47.00 ms² (p<0.05, t=2,15), the high-frequency component of the spectrum demonstrated improvement by 176.03 ms² (p<0.001, t=4,66), the LF/HF ratio was better by 1.18 units (p<0.01, t=3,14), the index of centralization (IC) was superior by 1.11 unit (p<0.01, t=3,02), the amplitude of mode (Amo) exhibited improvement by 18.00% (p<0.01, t=5,05), the stress index was superior by 133.97 units (p<0.001, t=5,88), the index of regulatory system activity was better by 1.79 units (p<0.01, t=3,22), the percentage contribution of the low-frequency component of the spectrum (LF) was improved by 12.70% (p<0.001, t=3,97), and the high-frequency component of the spectrum (HF) was superior by 9.74% (p<0.001, t=3,53). Conclusions: the results show that the inclusion of toning and relaxing Pilates techniques during the pedagogical experiment had a positive effect on improving flexibility, strength, balance, coordination, and increasing the functional state of the autonomic nervous system in women of complex coordination sports in the preparatory period of specialized basic training.